The Growth Range Equivalence Problem for D0L Systems is Decidable - Berstel, Jean (DAIMI Report Series, 1975)
The decidability of equivalence problems for DOL systems has been studied in various papers. One of the questions left open in these papers, is the decidability of what one might call the growth range equivalence problem. Two DOL systems are said to be equivalent if the ranges of their growth functions coincide. This problem is proved to be decidable. Published in: A. Lindenmayer & G. Rozenberg (ed.) Automata, Languages and Development, North-Holland, 1976.